Identification of volatile compounds of Clinopodium odorum (Lamiaceae): a comparison between HSSPME and classic hydrodistillation - Vázquez, Ana María (2014)
In the present work an analytical methodology to micr o scale based on the use of the HS - SPME/GC - MS to determine volatile compounds present in Clinopodium odorum (Griseb.) Harley (Lamiaceae)was optimized and settled differences and similarities with its essential oil. A systematic description of the volatile components of flowers, stems, leaves and combined aerial parts (whole plant) was constructed via GC - MS analyses of HS - SPME adsorbed compounds and of essential oils obtained through hydrodistillation of the same tissues. Pulegone was the main component of b oth the HS - SPME analysis and essential oil analysis. In addition, piperitenone oxide and piperitone oxide were the other main components in the essential oil whereas in the HS - SPME analysis cis - isopulegone and menthone prevailed. The HS - SPME method can ach ieve comparable results to those obtained by essential oil analysis, by using very fewer samples, a shorter extraction time and a much simpler procedure.